A More Rapid, Sensitive, and Specific HPLC-MS/MS Method for Nifedipine Analysis in Human Plasma and Application to a Pharmacokinetic Study - Chen, R.; Huang, J.; Lv, C.; Wei, C.; Li, R.; Yuan, G.; Liu, X.; Wang, B.; Guo, R. (Drug Research, 2013)
A more rapid, sensitive and specific high-performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS) was developed and validated for the quantification of nifedipine in human plasma, and applied to the pharmacokinetic study of nifedipine in Chinese healthy volunteers. Nifedipine and internal standard (IS) acetaminophen in plasma were extracted with ethyl acetate, separated on a C18 (150 mm×4.6 mm, 5 µm) reversed-phase column, eluted with acetonitrile mixed with 5 mM ammonium acetate solution (pH=6.62) (60:40, v/v), ionized by negative ion pneumatically assisted electrospray and detected in the multi-reaction monitoring mode using precursor→product ions of m/z 354.1→222.2 for nifedipine and 150.1→107.1 for the IS. A single oral dose of 20 mg nifedipine sustained release tablets and blood samples (4 mL) was collected before and 1, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 8, 12, 24, and 36 h after administration. The main pharmacokinetic parameters of nifedipine, as Tmax, t1/2α, t1/2β, t1/2z, Cmax, AUC0~36, AUC0~∞ were 2.80±0.50 h, 6.78±2.52 h, 6.82±2.53 h, 6.69±2.22 h, 76.69±19.51 (ng/mL), 546.49±162.28 (ng · h/mL) and 564.05±176.74 (ng · h/mL), respectively. The calibration curve was linear over the concentration range of 0.17–102 ng/mL (r2>0.99, n=5) with a lower limit of quantification (LLOQ) of 0.17 ng/mL. The intra- and inter-day precision was less than 15% for all quality control samples at concentrations of 0.42, 6.53 and 81.60 ng/mL and the accuracy (relative error, RE) was  − 3.92% to 7.31% at 3 quality control levels. The specificity, matrix effect, recovery, sensitivity, linearity, accuracy, precision and stabilities were validated, and can fulfill the requirement of pharmacokinetic study of nifedipine sustained release tablets in Chinese volunteers.
Keywords: nifedipine; HPLC-MS/MS; pharmacokinetics; acetaminophen